Nonlinear matter spectra in coupled quintessence - Saracco, F.; Pietroni, M.; Tetradis, N.; Pettorino, Valeria; Robbers, G. (Physical review. D, Particles, fields, gravitation, and cosmology, 2010)
We consider cosmologies in which a dark-energy scalar field interacts with cold dark matter. The growth of perturbations is followed beyond the linear level by means of the time-renormalization-group method, which is extended to describe a multicomponent matter sector. Even in the absence of the extra interaction, a scale-dependent bias is generated as a consequence of the different initial conditions for baryons and dark matter after decoupling. The effect is enhanced significantly by the extra coupling and can be at the 2%-3% level in the range of scales of baryonic acoustic oscillations. We compare our results with N-body simulations, finding very good agreement.